Altitude Control for Variable Load Quadrotor via Learning Rate Based Robust Sliding Mode Controller - Zhenbao Liu; Xubo Liu; Jie Chen; Chen Fang (IEEE Access, 2019)
This paper aims to solve the problem of altitude control of the variable load quadrotor unmanned aerial vehicle. Generally, the controller parameters of the quadrotor are adjusted for constant load and external disturbance factors. However, whether in military fields or civilian fields, the quadrotor will encounter variable load situations, such as throwing weapons or delivering express. Variable load as a large internal disturbance factor results in control instability. Toward this end, a novel robust sliding mode controller SMC) is designed to track the desired trajectory promptly under variable load condition while restraining the chattering problem. This novel controller consists of learning rate-based sliding mode surface and inverse hyperbolic function-based adaptive sliding mode reaching law. It is worth mentioning that a mass estimation algorithm is added to the proposed novel SMC to estimate the real-time mass of the quadrotor in the air, which improves the quadrotor's performance in restraining the large variable load disturbance impact. In addition, the altitude control law is derived on the basis of the Lyapunov stability theory. Finally, the simulation and experimental results are carried out to show the effectiveness and robustness of the proposed controller in terms of altitude tracking, mass estimation, and disturbance resistance.